2007
DOI: 10.1093/nar/gkm1096
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated cleavage of tRNAs in the bacterium Streptomyces coelicolor

Abstract: The ability to sense and respond to environmental and physiological signals is critical for the survival of the soil-dwelling Gram-positive bacterium Streptomyces coelicolor. Nutrient deprivation triggers the onset of a complex morphological differentiation process that involves the raising of aerial hyphae and formation of spore chains, and coincides with the production of a diverse array of clinically relevant antibiotics and other secondary metabolites. These processes are tightly regulated; however, the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 46 publications
4
116
0
4
Order By: Relevance
“…Below the mature tRNA bands, there are additional bands of intermediate size (35-60 nt long) that could correspond to the tRNA cleavage products that were reported recently (Lee and Collins 2005;Haiser et al 2008;Jochl et al 2008;Kawaji et al 2008;Li et al 2008;Thompson et al 2008;Zhang et al 2009). tRF-1001 was also measured by splinted ligation assays (Supplemental Fig.…”
Section: Expression Of Trfs Validated By Other Techniquesmentioning
confidence: 53%
See 1 more Smart Citation
“…Below the mature tRNA bands, there are additional bands of intermediate size (35-60 nt long) that could correspond to the tRNA cleavage products that were reported recently (Lee and Collins 2005;Haiser et al 2008;Jochl et al 2008;Kawaji et al 2008;Li et al 2008;Thompson et al 2008;Zhang et al 2009). tRF-1001 was also measured by splinted ligation assays (Supplemental Fig.…”
Section: Expression Of Trfs Validated By Other Techniquesmentioning
confidence: 53%
“…tRNA fragments of 30-35 nt have been identified in bacteria, fungi, plants, and animals (Lee and Collins 2005;Haiser et al 2008;Jochl et al 2008;Kawaji et al 2008;Li et al 2008;Thompson et al 2008;Zhang et al 2009). These tRNA fragments are different from the ones reported here in that they are derived from a cleavage at or around the anti-codon loop by Rny1p in yeast (Thompson and Parker 2009) or angiogenin in humans (Yamasaki et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, in both cleavage scenarios, the stability of the two generated tRNA halves can be asymmetric and change within the same organism, depending on the encountered stress condition and life stage. 42,46 This is well exemplified in two independent transcriptome studies in the unicellular eukaryote Trypanosoma cruzi. Franzen et al detected 88.9% of the tRNA halves deriving from the 3′ part of the genuine tRNA of epimastigotic organisms, with a preference for tRNA His .…”
Section: Trna In Piecesmentioning
confidence: 81%
“…40 Conspicuously, two different kinds of cleavage phenomena have been observed. While global tRNA cleavage correlated with codon usage in organisms like Streptomyces coelicolor, 41,42 other groups reported on isoacceptor-specific preferences. Here no correlation between targeted tRNAs and their number of genes, their cellular copy number, or the codon usage, has been found.…”
Section: Trna In Piecesmentioning
confidence: 99%
“…Similar tRNA cleavages have been previously described in other systems. In Tetrahymena, tRNA fragments were observed during amino acid starvation (Lee and Collins 2005), and Haiser et al (2008) have demonstrated developmental-specific cleavage of tRNAs in the bacterium Streptomyces coelicolor. Recent data from large-scale small-RNA sequencing studies have also identified cleaved tRNAs in human cells (Kawaji et al 2008) and in Aspergillus (Jochl et al 2008).…”
Section: Discussionmentioning
confidence: 99%